ASSESSING MUTĀBARAH MEDIATION IN EMPOWERING SUSTAINABLE AGRIBUSINESS DEVELOPMENT FOR INDONESIAN MILLENNIAL FARMERS - Nur Fadilah; Syaparuddin Razak; Zulkifli Zulkifli (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2026)
This study aims to examine the mediating role of Mutābarah (perseverance) in sustainable agribusiness development among Indonesian millennial farmers. Grounded in the Theory of Planned Behavior and Character-Based Entrepreneurship Theory, it analyzes how attitudes toward behavior, subjective norms, and entrepreneurial character influence agribusiness development directly and indirectly through Mutābarah. A quantitative explanatory approach was employed using survey data from 150 millennial farmers in Bone Regency, Indonesia. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results show that attitudes, subjective norms, and entrepreneurial character significantly influence Mutābarah. In turn, Mutābarah has a significant positive effect on agribusiness development. Direct effects of these variables on agribusiness development are also observed, with varying levels of significance. Mediation analysis indicates that Mutābarah partially mediates the relationships, confirming its role in translating behavioral and entrepreneurial factors into sustained agribusiness performance.These findings highlight the importance of perseverance grounded in ethical values in strengthening agribusiness sustainability and offer practical implications for character-based empowerment programs.